Fusion to Flaviviral Leader Peptide Targets HIV-1 Reverse Transcriptase for Secretion and Reduces Its Enzymatic Activity and Ability to Induce Oxidative Stress but Has No Major Effects on Its Immunogenic Performance in DNA-Immunized Mice - Anastasia Latanova; Stefan Petkov; Yulia Kuzmenko; Athina Kilpeläinen; Alexander Ivanov; Olga Smirnova; Olga Krotova; Sergey Korolev; Jorma Hinkula; Vadim Karpov; Maria Isaguliants; Elizaveta Starodubova (Journal of Immunology Research)
Reverse transcriptase (RT) is a key enzyme in viral replication and susceptibility to ART and a crucial target of immunotherapy against drug-resistant HIV-1. RT induces oxidative stress which undermines the attempts to make it immunogenic. We hypothesized that artificial secretion may reduce the stress and make RT more immunogenic. Inactivated multidrug-resistant RT (RT1.14opt-in) was N-terminally fused to the signal providing secretion of NS1 protein of TBEV (Ld) generating optimized inactivated Ld-carrying enzyme RT1.14oil. Promotion of secretion prohibited proteasomal degradation increasing the half-life and content of RT1.14oil in cells and cell culture medium, drastically reduced the residual polymerase activity, and downmodulated oxidative stress. BALB/c mice were DNA-immunized with RT1.14opt-in or parental RT1.14oil by intradermal injections with electroporation. Fluorospot and ELISA tests revealed that RT1.14opt-in and RT1.14oil induced IFN-γ/IL-2, RT1.14opt-in induced granzyme B, and RT1.14oil induced perforin production. Perforin secretion correlated with coproduction of IFN-γ and IL-2 (R=0,97). Both DNA immunogens induced strong anti-RT antibody response. Ld peptide was not immunogenic. Thus, Ld-driven secretion inferred little change to RT performance in DNA immunization. Positive outcome was the abrogation of polymerase activity increasing safety of RT-based DNA vaccines. Identification of the molecular determinants of low cellular immunogenicity of RT requires further studies.